PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH KEJURUAN SE-KABUPATEN HALMAHERA UTARA - Itje, Tomi (Universitas Negeri Makassar, 2018)
The purpose of this study was to determine the influence of the principal's leadership, organizational climate and work motivation on teacher performance in Vocational Schools in North Halmahera Regency both partially and simultaneously. Data from the analysis in this study shows that the Principal Leadership is in the good category in the implementation task. Besides that, the organizational climate shows good creation of a safe, comfortable atmosphere and hangs up the fun learning process. While work motivation both internal and external encouragement reaches the desired expectations. Based on multiple regression tests partially shows that the leadership of the principal, organizational climate does not have a positive influence on teacher performance. While work motivation has a positive and partial effect on the performance and simultaneously leadership of the principal, organizational climate, work motivation of this variable together have a positive effect on teacher performance.